Sildenafil citrate to improve colour doppler indices in patient with pre-eclampsia: a path less taken - Vora, Priyanka H.; Choudhary, Rana A.; Ganla, Kedar N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Presented a case of high-risk pregnancy of an elderly primigravida who had abnormal colour doppler indices. Addition of sildenafil citrate lead to improvement of colour doppler indices and growth parameters, thus prolonging the period of gestation by 6 weeks. This led to decreased neonatal ICU stay and reduction in neonatal morbidity.